International-Business Political Behavior: New Theoretical Directions - Boddewyn, Jean J.; Brewer, Thomas L. (Academy of Management Review, 1994)
Alternative assumptions are advanced regarding the political nature of international business and the role of government as a factor of production, which firms must manage in their international value-added chains. Based on a model of business political behavior, various propositions are developed regarding the interactions among firm, industry, and nonmarket factors as well as the impact they have on various forms and intensities of political behavior, as affected by strategic objectives. Finally, the strategic-theorizing implications of such behavior are discussed in the context of the recent emphasis on resource-based models of strategy management.